Implementation of Qaulan Baligho Communication of Religious Instructors in Building an Understanding of Religious Moderation in Panai Hilir Sei Berombang Labuhanbatu District - Rubino; Tuti Restilia (Sean Institute, 2022)
This study aims to determine the role of communication of Islamic leaders in building an understanding of religious moderation in Muslim communities in Panai Hilir Sei Berombang District, Labuhanbatu. This research uses a type of descriptive qualitative research to achieve the goals referred to above. Researchers collect data through observation, documentation and interviews. The informants of this research were Islamic leaders in Panai Hilir Sei Berombang District, Labuhanbatu. The results of this study state that the communication of Islamic figures plays a very important role in building an understanding of religious moderation in Muslim communities in Panai Hilir Sei Berombang District, Labuhanbatu. Creating harmony between religious communities which are gathered in the word moderation, namely tolerance, deliberation on issues that are not basic understandings but the common good, become a mediator between people of different beliefs and cultures and quickly respond and adopt policies on issues that develop in society so that harmony can be re-created by respecting each other and giving rights as Indonesian citizens. But by continuing to invite goodness and uphold justice.